PERAN PENGELOLA PERSATUAN ORANG TUA MURID DAN GURU PPT BUNGA TERATAI PADA PENURUNAN STUNTING MELALUI GERAKAN SADAR GIZI SEIMBANG - Azminah, Suhartini Nurul; Oktaviani, Rizki Nur; Zuroida, Aironi (Jurnal Terapan Abdimas, 2025)
Abstract. The purpose of this community service is to handle stunting in PPT Bunga Teratai students through the role of managers, both the principal, the Parent and Teacher Association (POMG) by implementing the "Balanced Nutrition Awareness Program". The implementation of this community service activity involved 2 Lecturers from STKIP Bina Insan Mandiri and 1 Lecturer in Psychology from Wijaya Putra University and STKIP Bina Insan Mandiri Surabaya Students. The subjects in this service are managers, educators, and guardians of PPT Bunga Teratai which is located at Jalan Tenggumung Baru No.225 RW. IX Pegirian Village, Semampir District. Surabaya. The method of implementing this community service activity is carried out in 5 stages, namely problem identification, action planning, implementation of empowerment of beginner communities, observation, and reflection. The results of this community service activity are that there was a 50% decrease in students experiencing stunting, which initially amounted to 10 students to 5 students. Educators and student associations played a role in providing additional food which was carried out once every 2 weeks according to a healthy menu, and creating a healthy canteen with a healthy menu which was carried out once a month.     Abstrak. Tujuan melakukan pengabdian kepada masyarakat ini adalah melakukan penanganan stunting pada siswa PPT Bunga Teratai melalui peran pengelola baik kepala sekolah, Persatuan Orang Tua Murid dan Guru (POMG) dengan melaksanakan “Program Sadar Gizi Seimbang”. Pelaksanaan kegiatan pengabdian ini melibatkan 2 Dosen dari STKIP Bina Insan Mandiri dan 1 Dosen Psikologi Universitas Wijaya Putra serta Mahasiswa STKIP Bina Insan Mandiri Surabaya. Subjek dalam pengabdian ini yaitu pengelola, pendidik, dan wali murid dari PPT Bunga Teratai yang berlokasi di Jalan Tenggumung Baru No.225 RW. IX Kelurahan Pegirian, Kecamatan Semampir. Surabaya. Adapun metode pelaksanaan kegiatan pengabdian kepada masyarakat ini dilakukan dalam 5 tahapan yaitu identifikasi masalah, perencanaan tindakan, pelaksanan pemberdayaan Masyarakat pemula, observas, dan refleksi. Adapun hasil dari kegiatan pengabdian ini, bahwa mengalami penurunan 50% anak didik yang mengalami stunting yang mulanya 10 anak didik menjadi 5 anak, pendidik dan persatuan murid berperan dalam pemberian makanan tambahan yang dilaksanakan 2 minggu sekali sesuai dengan menu sehat, dan membuat kantin sehat dengan menu sehat yang dilaksanakan 1 bulan sekali.